Effect of helix angle in cross-roll arrangements of bar straightening process with kinematic reverse bending - Sanjib, Roy; Kuran, Arun (Journal of Production Engineering, 2022)
Round bars produced in industries are often found compromised with degree of straightness. In many small or medium size industries the problem of straightness is often addressed somewhat manually, which is indeed a slow and cumbersome process and lacks quality and precision. To speed up the process, it is necessary to go for mechanized system i.e. deployment of straightening machine. However, straightening machine indeed helps in perfect processing of operation and quality aspects which can be systematically controlled through various parameters involved in the process. An attempt has been made in this paper to look into the effect of helix angle of the cross-roll arrangement in the process based on the equations developed by former researchers in this field.